Association of neighbourhood disadvantage and individual socioeconomic position with all-cause mortality: a longitudinal multicohort analysis. (May 2022) - Ribeiro, Ana Isabel; Fraga, Silvia; Severo, Milton; Kelly-Irving, Michelle; Delpierre, Cyrille; Stringhini, Silvia; Kivimaki, Mika; Joost, Stéphane; Guessous, Idris; Severi, Gianluca; Giles, Graham; Sacerdote, Carlotta; et al.
Summary: Background: Few studies have examined the interactions between individual socioeconomic position and neighbourhood deprivation and the findings so far are heterogeneous. Using a large sample of diverse cohorts, we investigated the interaction effect of neighbourhood socioeconomic deprivation and individual socioeconomic position, assessed using education, on mortality. Methods: We did a longitudinal multicohort analysis that included six cohort studies participating in the European LIFEPATH consortium: the CoLaus (Lausanne, Switzerland), E3N (France), EPIC-Turin (Turin, Italy), EPIPorto (Porto, Portugal), Melbourne Collaborative Cohort Study (Melbourne, VIC, Australia), and Whitehall II (London, UK) cohorts. All participants with data on mortality, educational attainment, and neighbourhood deprivation were included in the present study. The data sources were the databases of each cohort study. Poisson regression was used to estimate the mortality rates and associations (relative risk, 95% CIs) with neighbourhood deprivation (Q1 being least deprived to Q5 being the most deprived). Baseline educational attainment was used as an indicator of individual socioeconomic position. Estimates were combined using pooled analysis and the relative excess risk due to the interaction was computed to identify additive interactions. Findings: The cohorts comprised a total population of 168 801 individuals. The recruitment dates were 2003–06 for CoLaus, 1989–91 for E3N, 1992–98 for EPIC–Turin, 1999–2003 for EPIPorto, 1990–94 for MCCS, and 1991–94 for Whitehall II. We use baseline data only and mortality data obtained using record linkage. Age-adjusted mortality rates were higher among participants residing in more deprived neighbourhoods than those in the least deprived neighbourhoods (Q1 least deprived neighbourhoods, 369·7 per 100 000 person-years [95% CI 356·4–383·2] vs Q5-most deprived neighbourhoods 445·7 per 100 000 person-years [430·2–461·7]), but the magnitude of the association varied according to educational attainment (relative excess risk due to interaction=0·18, 95% CI 0·08–0·28). The relative risk for Q5 versus Q1 was 1·31 (1·23–1·40) among individuals with primary education or less, but less pronounced among those with secondary education (1·12; 1·04–1·21) and tertiary education (1·16; 1·07–1·27). Associations remained after adjustment for individual-level factors, such as smoking, physical activity, and alcohol intake, among others. Interpretation: Our study suggests that the detrimental health effect of living in disadvantaged neighbourhoods is more pronounced among individuals with low education attainment, amplifying social inequalities in health. This finding is relevant to policies aimed at reducing health inequalities, suggesting that these issues should be addressed at both the individual level and the community level. Funding: The European Commission, European Regional Development Fund, the Portugese Foundation for Science and Technology.